RFID Medication Management System in Hospitals - El Abkari, Safae; Jilbab, Abdelilah; El Mhamdi, Jamal (International Journal of Online and Biomedical Engineering (iJOE), 2020)
One of the primary concerns of the World Health Organization is the improvement of medical care by reducing adverse events in the medication process and enhancing the safety of patients. These issues are mainly related to the management of expensive and high-risk medicines in hospitals. In this paper, we enhanced medication management by minimizing the possibility of medication errors from its prescription-validation to its preparation. For this purpose, we designed a hospital and pharmacy services management system by employing digital signature using Radio Frequency IDentification technology. Our proposed system is equipped with ESP8266 modules, RFID readers and tags which allow the detection of taking medications and ensures an automated medication management.